The excitable nature of polymerizing actin and the Belousov-Zhabotinsky reaction - Riedl, Michael; Sixt, Michael (Frontiers in Cell and Developmental Biology, 2023)
The intricate regulatory processes behind actin polymerization play a crucial role in cellular biology, including essential mechanisms such as cell migration and or cell division. However, the selforganizing principles governing actin polymerization are still poorly understood. In this perspective article, we compare the Belousov-Zhabotinsky (BZ) reaction, a classic and well understood chemical oscillator known for its self-organizing spatiotemporal dynamics, with the excitable dynamics of polymerizing actin. While the BZ reaction originates from the domain of inorganic chemistry, it shares remarkable similarities with actin polymerization, including the characteristic propagating waves, which are influenced by geometry and external fields, and the emergent collective behavior.Starting with a general description of emerging patterns, we elaborate on single droplets or cell-level dynamics, the influence of geometric confinements and conclude with collective interactions.Comparing these two systems sheds light on the universal nature of self-organization principles in both living and inanimate systems.